2001
DOI: 10.5795/jjscc.40.121
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of cdk 2 and Ki-67 in human endometrial carcinoma.

Abstract: Immunohistochemical expression of cdk 2 and Ki-67 in human endometrial carcinoma Makoto AKABOSHI1), C.T., I.A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Tumor cells with >5% positive staining were classified as positive for p14 ARF . The results of p14 ARF expression were compared with those of Ki-67 (19), cyclin A (20), cyclin D1 (21), cyclin E (22), cdk2 (19), p27 (23), and p53 (24) expression.…”
Section: Evaluation Of Immunohistochemistrymentioning
confidence: 99%
“…Tumor cells with >5% positive staining were classified as positive for p14 ARF . The results of p14 ARF expression were compared with those of Ki-67 (19), cyclin A (20), cyclin D1 (21), cyclin E (22), cdk2 (19), p27 (23), and p53 (24) expression.…”
Section: Evaluation Of Immunohistochemistrymentioning
confidence: 99%
“…The results of PR-A and -B expressions were compared with those of Ki-67, cyclin E, cyclin A, cyclin D1, cdk2, p27 and p53, which had been analyzed at our laboratory [6][7][8][9][10][11]. In brief, for immunostaining of Ki-67, cyclin E, cyclin A, cyclin D1, cdk2, p27 and p53, rabbit polyclonal anti-Ki-67 antibody (DAKO, 1:50 dilution), mouse monoclonal anti-cyclin E antibody (13A3, Novocastra, 1:40 dilution), mouse monoclonal anti-cyclin A antibody (6E6, Novocastra, 1:100 dilution), mouse monoclonal anti-cyclin D1 antibody (DCS-6, Oncogene, 1:80 dilution), rabbit polyclonal anti-cdk2 antibody (M2, Santa Cruz Biotechnology, 1:2000 dilution), mouse monoclonal anti-p27 antibody (1B4, Novocastra, 1:200 dilution) and mouse monoclonal anti-p53 antibody (DO-7, Novocastra, 1:80 dilution) were used for a labeled streptavidin-biotin methods (LSAB kit, DAKO).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Traditional factors associated with its prognosis include tumor grade, depth of uterine myometrial invasion and stage [5]. We previously showed that cell cycle-regulatory proteins such as Ki-67, cyclin E, cyclin A, cyclin D1, cyclin-dependent kinase (cdk) 2, p27 and p53 were correlated with the malignant potential of endometrial adenocarcinoma [6][7][8][9][10][11]. In addition, the most extensively studied biologic markers in endometrial carcinoma are ER and PR.…”
Section: Introductionmentioning
confidence: 99%
“…Positive staining was evaluated by counting approximately 1,000 cells in high-power fields and was expressed as the labeling index (LI), which was regarded as the percentage of positive nuclei. The result of skp2 expression was compared with those of p27, Ki-67, cdk2, cyclin A, cyclin D1, cyclin E, p53 and PTEN, which had been analyzed in our laboratory Akaboshi et al 2001;Kyushima et al 2002;Nishimura et al 2004;Kato et al 2003;Fujisawa et al 2001;Kimura et al 2004). …”
Section: Immunohistochemistrymentioning
confidence: 99%